Konsep Bentuk Perusahaan Pertambangan Mineral dan Batubara dalam Perspektif Undang-Undang Dasar 1945 - Hayat Hayat (Jurnal Konstitusi, 2020)
The concept of mineral and coal mining management provided by business entities, cooperatives and individuals as regulated in Law No.3 of 2020 concerning Amendments to Law No.4 of 2009 concerning Mineral and Coal Mining which is managed under the concept of a Mineral and Coal mining company. constitution based on the 1945 Constitution. The research method used is juridical normative, resulting in that the form of mineral and coal mining companies by the 1945 Constitution is a business entity, cooperative or individual listed in the Mineral and Coal Mining Law. which has a cooperative nature by the 1945 Constitution.